Green pavement strategies for Malaysia / Ahmad Kamil Arshad - Arshad, Ahmad Kamil (UiTM Press, 2023)
The basis for this book originally stemmed from my passion to develop better and sustainable pavement for roads and highways. This book discusses on pavements, a specialised area of highway engineering and covers on the sustainable aspects of the pavement life cycle, including design, construction, maintenance and rehabilitation phases. The emphasis of this book is on the use of sustainable pavement materials which forms the pavement structure. Research on pavement materials is important as the durability of the pavement structure, hence, its sustainability is dependent on the materials used. This book is important as it contains information on the various research undertaken by the author to improve the sustainability of pavement materials, such as bitumen modification using polymers and the use of waste materials such as reclaimed asphalt pavement to reduce asphalt mix production costs. Worldwide, research on pavement materials is increasing as there is a need to improve the durability of the road pavement which is subjected to the ever-increasing loads in terms of numbers of axle repetitions, load intensity and different climatic conditions. This book will be of interest to the engineers involved in pavement construction and maintenance as it provides comprehensive information on sustainable pavement materials research.